A Static Picture of the Relaxation and Intersystem Crossing Mechanisms of Photoexcited 2-Thiouracil - Mai, Sebastian (J Phys Chem A, 2015)
[Image: see text] Accurate excited-state quantum chemical calculations on 2-thiouracil, employing large active spaces and up to quadruple-ζ quality basis sets in multistate complete active space perturbation theory calculations, are reported. The results suggest that the main relaxation path for 2-thiouracil after photoexcitation should be S(2) → S(1) → T(2) → T(1), and that this relaxation occurs on a subpicosecond time scale. There are two deactivation pathways from the initially excited bright S(2) state to S(1), one of which is nearly barrierless and should promote ultrafast internal conversion. After relaxation to the S(1) minimum, small singlet–triplet energy gaps and spin–orbit couplings of about 130 cm(–1) are expected to facilitate intersystem crossing to T(2), from where very fast internal conversion to T(1) occurs. An important finding is that 2-thiouracil shows strong pyramidalization at the carbon atom of the thiocarbonyl group in several excited states.